Drying Kinetics of Banana Chips: A Modeling Approach - Hermanuadi, Didik; Iswahyono, Iswahyono; Kurniawati, Elly; Djamila, Siti; Bahariawan, Amal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The primary goal of this research is to identify and evaluate the most suitable thin-layer drying model to effectively interpret the drying characteristics of banana chips and determine moisture diffusivity at different drying temperatures. The study utilized physiologically mature â€œkapokâ€ bananas from the local market in Jember Regency. A flash dryer with a 4000-watt electric heating system was used, equipped with a blower for air circulation, an exhaust fan to expel water vapor. The bananas were processed into chips with a thickness of 1 mm. A total of 2000 g of banana chips were dried at constant temperature according to treatment conditions (air velocity 3.2 m/s, drying at temperatures of 60, 70, and 80Â°C). The study found that higher drying temperatures (80Â°C) achieved the highest initial drying rate (35.9% in 30 min) compared to 60Â°C (28.0%) and 70Â°C (22.0%). However, the drying rate gradually decreased at all temperatures. The drying kinetics of banana chips at 60, 70, and 80Â°C aligned well with the modified Midilli model. Effective moisture diffusivity values for banana chips at 60, 70, and 80Â°C were 4.947E-9 mÂ²/s, 5.165(10â€“9) mÂ²/s, and 5.756(10â€“9) mÂ²/s, respectively, indicating that drying at 80Â°C was the most effective. The effective moisture diffusivity value showed a strong correlation with air velocity, drying temperature, material thickness, RH, and specific material attributes. Â  Keywords:Â Banana,Â Diffusivity,Â Drying,Â Thin layer drying,Â Modified Midilli Model.